Emergence of resilience based on social context : a study on baboons (Singapore zoo) - Chua, Alex Rui Chuen (2015)
Amongst adult male hamadryas baboons (Papio hamadryas), low-ranking males suffer from increased stress levels, while alliances improve the Resource Holding Potential of an individual. This study aims to determine if individual relationships between adult male hamadryas baboons exist, and how stress resilience is affected by it. Subjects chosen were captive hamadryas baboons from the Singapore Zoo, where their behaviors were observed. Sixteen coalitions were recorded, showing that 3 subjects were frequently targeted, while 9 subjects were frequent supporters of these coalitions. The other subjects rarely participated in coalitions. Frequently targeted subjects were never supporters, demonstrating that sustained relationships between individual baboons exist. There were no statistically significant differences in rate of greetings performed and received between the 3 groups, showing that frequently targeted males may not suffer from poor relationships with other males. However, one particular subject had a very low rate of receiving greetings, and was also determined to be low-ranking and stress vulnerable. Males in the frequent supporters group received greetings more than performed, with 2 of 3 subjects considered as higher-ranking. As a group, they could possibly be more stress resilient as well. Hence, stress resilience could arise from having positive relationships with other males.